2020
DOI: 10.1038/s41467-020-16214-8
|View full text |Cite
|
Sign up to set email alerts
|

Unique properties of a subset of human pluripotent stem cells with high capacity for self-renewal

Abstract: Archetypal human pluripotent stem cells (hPSC) are widely considered to be equivalent in developmental status to mouse epiblast stem cells, which correspond to pluripotent cells at a late post-implantation stage of embryogenesis. Heterogeneity within hPSC cultures complicates this interspecies comparison. Here we show that a subpopulation of archetypal hPSC enriched for high self-renewal capacity (ESR) has distinct properties relative to the bulk of the population, including a cell cycle with a very low G1 fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 77 publications
8
73
0
Order By: Relevance
“…In human, FS cells appear related to a somewhat earlier stage of postimplantation epiblast than conventional hPSCs. However, conventional hPSCs are not equivalent to EpiSCs (Lau et al, 2020), and the differences from FS cells are less marked.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In human, FS cells appear related to a somewhat earlier stage of postimplantation epiblast than conventional hPSCs. However, conventional hPSCs are not equivalent to EpiSCs (Lau et al, 2020), and the differences from FS cells are less marked.…”
Section: Discussionmentioning
confidence: 93%
“…At the transcriptome level human FS cells differ from populations of conventional hPSCs cultured in E8 or other conditions, but these differences are relative rather than absolute. Heterogeneity and hierarchical substructure has been described in hPSC cultures (Allison et al, 2018;Hough et al, 2009;Hough et al, 2014;Lau et al, 2020;Nakanishi et al, 2019) and we cannot exclude the presence of formative stem cells at some frequency. Human FS cells and conventional hPSCs may be a continuum spanning stages of postimplantation epiblast.…”
Section: Limitations Of Studymentioning
confidence: 91%
See 1 more Smart Citation
“…Analysis of the expression of G1, S and G2/M-specific genes indicated that clusters 0 and 1 had higher expression of G2/M and proliferative genes (Fig. 6D, E), suggesting these are highly proliferative cells identified previously (Nguyen et al 2018;Lau et al 2020), positive for EPCAM, CD9 and PODXL (GCTM2) (Fig. 6E, and Supplemental Fig.…”
Section: Single Cell Rna-seq Expression Of Lincrnas Heterogeneity Inmentioning
confidence: 95%
“…4). Indeed, a recent study has shown that subpopulations of human pluripotent stem cells with high capacities for self-renewal have greater chromatin accessibility at regions of pluripotency TF binding (Lau et al 2020). Moreover, evidence from zebrafish embryos indicates that TFs are in passive competition with core histones for bind-ing to DNA, and the nuclear ratio between histones and DNA-binding factors is important for the onset of zygotic transcription (Joseph et al 2017).…”
Section: Chromatin Remodeling and Pluripotencymentioning
confidence: 99%